2018
DOI: 10.7717/peerj.5952
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-histological development of the somatic embryos of Typha domingensis

Abstract: BackgroundSustainable methods of propagation of Typha domingensis through somatic embryogenesis can help mitigate its current condition of ecological marginalization and overexploitation. This study examined whether differentiation up to coleoptilar embryos could be obtained in an embryogenic line proliferated with light and high auxin concentration.MethodsMurashige and Skoog medium at half ionic strength and containing 3% sucrose and 0.1% ascorbic acid was used for the three embryogenic phases. Induction star… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…These treatments included growth on MS0.1 semisolid culture medium (Figure 2A), growth in liquid MS0.1 medium without growth regulators (Figure 2B), or growth in purified sterile water alone (Figure 2C); in addition, all the treatments included ascorbic acid. Both liquid systems produced friable tissue (Figure 2B,C) with crumbly rhizoclones suitable for the induction of embryogenic callus with embryos in several developmental stages (Figure 2D), as previously reported [33]. Moreover, further experiments revealed that the rhizoclones induced in rhizotron systems, incubated in the dark, yielded a large amount of unpigmented embryos in the scutellar and oblong morphological stages of development (Figure 2D-F), which were suitable for studying the induction of hairy roots by cocultivation with A. rhizogenes (Figure 2H).…”
Section: Resultssupporting
confidence: 81%
See 4 more Smart Citations
“…These treatments included growth on MS0.1 semisolid culture medium (Figure 2A), growth in liquid MS0.1 medium without growth regulators (Figure 2B), or growth in purified sterile water alone (Figure 2C); in addition, all the treatments included ascorbic acid. Both liquid systems produced friable tissue (Figure 2B,C) with crumbly rhizoclones suitable for the induction of embryogenic callus with embryos in several developmental stages (Figure 2D), as previously reported [33]. Moreover, further experiments revealed that the rhizoclones induced in rhizotron systems, incubated in the dark, yielded a large amount of unpigmented embryos in the scutellar and oblong morphological stages of development (Figure 2D-F), which were suitable for studying the induction of hairy roots by cocultivation with A. rhizogenes (Figure 2H).…”
Section: Resultssupporting
confidence: 81%
“…As previously reported [48], the adherence of Agrobacterium to the surface of embryos might have been improved by the acid pH (5.5) of the culture medium used in the coculture, the absence of accessory structures such as cutin in this type of tissue [47], or the addition of ascorbic acid to the culture system [49]. In addition, Agrobacterium has been reported to show enhanced virulence in the presence of phenolic compounds [50], such as those produced by T. domingensis embryos [33]. Thus, consistent with these results, the acid pH, addition of ascorbic acid, and liquid state of the coculture medium all favored biochemical adherence of the bacteria to the embryo surface, thereby enhancing the agrotransformation process.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations